School Refusal in Immigrants and Ethnic Minority Groups: A Qualitative Study of Adolescents' and Young Adults' Experiences - Brault, Camille; Thomas, Isaiah; Moro, Marie Rose; Benoit, Laelia (Frontiers in Psychiatry, 2022)
Background: School refusal is one cause of school absenteeism along with truancy, and the two can be difficult to distinguish. School absenteeism behaviors among students in transcultural situations (immigrants or children of immigrants) and from ethnic minority groups are subject to misdiagnosis and decreased access to care. To improve the care provided, this exploratory study addresses the experience of adolescents and young adults engaging in school refusal, from immigrant and ethnic minority groups. Methods: 16 participants between the ages of 16 and 20 years old presenting with school refusal were interviewed for this qualitative study. All participants were either immigrants, children of immigrants, or from an ethnic minority group. We conducted a qualitative analysis based on Interpretative Phenomenological Analysis. Results: Participants experienced school refusal as a loss of identity and as a failure to achieve what was perceived as parental expectations of success, which triggered feelings of worthlessness, shame, and guilt. The loss of a peer group, namely their classmates, as a result of school absenteeism was experienced as a marginalization from the larger society. Although participants denied having personally experienced racism, some of them recalled their parents experiencing racism at school. Conclusion: School refusal complicates identity construction, autonomy, and integration into society. For adolescents and young adults from immigrant and ethnic minority backgrounds, it also triggers guilt, transgenerational traumatic memories, and the fear of marginalization. In addition to validated therapies for school refusal, sociological, intersectional, and cross-cultural tools would be a valuable addition to treatment.